Potencial gravitacional lunar - Carvalho, Rafael Cunha de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We know that the orbit of a lunar satellite, and consequently its orbital lifetime is mainly inuenced by the gravitational field of the Moon, Earth and Sun. In this text we study the Lunar gravitational potential and its influence on the gravitational field. We adapted a program in order to map the Moon gravitational field. To that end it was necessary to develop a program that allows the simulation and mapping the lunar full potential. Our program was based on the program developed by Hélio Kuga, and adapted to our case (Moon). We used the model proposed by Konopliv et al. 2001, we proposed various degree and order expansions of spherical harmonics that served us to compare and validate our program

Sabemos que a órbita de um satélite lunar e, consequentemente, seu tempo de vida orbital é influenciado principalmente pelo campo gravitacional da Lua, Terra e Sol. Neste trabalho estudaremos o Potencial Gravitacional Lunar e sua influência sobre o campo gravitacional. Nós adaptamos um programa que possibilite mapear o campo gravitacional lunar. Nesse intuito foi necessário desenvolver um programa que permita a simulação e o mapeamento do potencial lunar completo. Nosso programa foi desenvolvido baseado no programa elaborado por Hélio Kuga, e adaptado para nosso caso (Lua). Utilizando o modelo proposto por Konopliv et al. 2001, propusemos diversas expansões de grau e ordem dos harmônicos esféricos que nos serviram para comparar e validar nosso programa
Keywords: Gravidade (Fisica); Lua; Potencial gravitacional; Satelites - Orbitas; Campos gravitacionais; Gravitational potential